EXPLORING THE IMPACT OF TRANSFORMATIONAL LEADERSHIP ON MOTIVATION: MEDIATED RESULTS OF ORGANIZATIONAL CULTURE - Panjaitan, Raya; Pinem, Neni Anita (UNIKA Santo Thomas, 2022)
Work motivation pertains to the factors that impact the initiation, direction, and persistence of activity in the workplace. Motivation in this work setting is strongly linked to organizational factors influenced by transformational leadership and organizational culture, which enhance organizational effectiveness. The test was conducted on public servants at the sub-district office in the Sidikalang district of North Sumatra. This research aims to investigate the correlation between transformational leadership and work motivation, and to evaluate organizational culture as a mediator between transformational leadership and work motivation. A quantitative non-probability sampling procedure was employed to acquire 45 respondents. Variable data is evaluated using a Likert scale. The data analysis method employs structural equation modeling (SEM) through the usage of SmartPLS 3.0. The analytical findings show that organizational culture has a mediating role in the relationship between transformational leadership and job motivation. Transformational leadership and organizational culture positively influence consumer satisfaction. The organization has combined transformational leadership and organizational culture to enhance employee work motivation, leading to improved organizational performance.